Analisis Kelayakan Usaha Rempeyek (Teriyummy) Di Desa Sengonagung Kecamatan Purwosari Kabupaten Pasuruan - Khasanah, Jamiyatul; Nugroho, Matheus (Jurnal Perikanan dan Kelautan, 2025)
This study aims to analyze the feasibility of the "TeriYummy" anchovy crackers business, a Micro, Small, and Medium Enterprise (MSME) pioneered by students of Yudharta University Pasuruan in Sengonagung Village. As a maritime country, Indonesia has abundant fisheries potential, one of which is anchovies, which are the main raw material for this product. This study uses a descriptive quantitative approach by analyzing five aspects of feasibility: market and marketing, technical, management, legal, and financial. Data collection was carried out through interviews, documentation, and literature studies. Financial analysis uses three main indicators, namely the Revenue Cost Ratio (RCR), Break-Even Point (BEP), and Return on Investment (ROI). The results of the study indicate that "TeriYummy" has strong market potential, supported by an effective hybrid marketing strategy, as evidenced by an increase in sales of up to 300% over a four-month period. Technically, the production process runs efficiently with adequate capacity. The management aspect is well structured, and this business has fulfilled all necessary legal requirements, including NIB, PIRT, and Halal Certificate. Financially, this business is highly profitable, with a Return on Assets (ROA) of 2.89, an average net profit of Rp 1,036,184 per month, and an ROI of 189%. Based on these findings, it is concluded that the "TeriYummy" business is highly feasible for further development.